(untitled) (Terr@ Plural, 2021)
Soil degradation caused by erosion is one of the biggest environmental problems. The objective is to analyze the erodibility factors, slope in the Gurgueia-Piauí River (BHRG) sub-basin. The Geographic Information System (GIS) QGIS and ArcGIS were used to prepare thematic maps. The average slope resulted as smooth wavy (42.1%), flat (27.8%) and wavy to strong wavy (19.9%) over the entire length of the sub-basin. Erodibility resulted in very high (41%) mainly in sectors with a predominance of Neossolos Quartzarênicos soils, on average (7.1%) in the South and Southwest and low (51.1%) of the area associated with soil of the type Dystrophic Yellow Latosol. The expansion of grain agribusiness associated with inadequate soil management in areas susceptible to erosion at BHRG can compromise long-term environmental, social and economic sustainability, with important appropriate agricultural techniques for the soil to optimize its use and sustainable production capacity.